Teatro Terapia em mulheres que sofreram violência pelo parceiro íntimo: uma visão da psicologia analítica - Rojas, Viviane Ramos (2024)
The definition of intimate partner violence (IPV) comprises behaviors that can be organized into four categories: physical violence; sexual violence; emotional, psychological, or moral abuse; and financial abuse. Exposure to IPV has been associated with negative outcomes for the mental health of victims, particularly with high levels of emotional suffering. In an effort to explore approaches suitable for treating women who have experienced IPV, the choice was made to investigate a specific technique of dramatherapy known as Autobiographical Therapeutic Performance – ATP, Pendzik (2020). The research aimed to analyze and assess the effects on women who have experienced IVP of a short intervention of drama therapy based on this technique. The study included a quantitative stage with results analyzed statistically, and a qualitative phase with outcomes analyzed symbolically, based on the theoretical framework of analytical psychology. Initial data from the experimental group (composed of 15 participants) and the control group (composed of 17 participants) were collected at T0, using the Intimate Partner Violence Scale and a sociodemographic questionnaire characterizing the violence suffered. Participants from the experimental group were assessed before and after the intervention (T0 and T1), using the following instruments: Rosenberg Self-Esteem Scale; Beck Depression Inventory; Shame Scale; Multidimensional Guilt Scale; and the Personal Questionnaire. Participants in the control group were assessed using the same instruments in the same interval. Qualitative analysis was based on methods proposed by Pendzik (2020) and Roesler (2018), also involving the analysis of categories of themes presented in scenes performed and emerging symbols. Quantitative results obtained through the scales indicated a statistically significant post-intervention improvement in the outcomes measured for the experimental group. There were no statistically significant differences in the control group. The Personal Questionnaire was analyzed quantitatively and assessed the frequency of negative and positive words expressed by participants, with results indicating a decrease in the frequency of negative words for the experimental group that was not observed in the control group. Qualitative analysis revealed that guilt, shame, self-esteem, and depression appeared in the performed scenes, associated with two broad themes: violence and liberation. Subthemes could be discerned, throwing light on the subjectivation of the experienced violence. In the progression of the performed scenes, a tendency toward a more determined attitude, resolution of conflicting outcomes, and development of more positive content in stories were observed. Working with imaginative and dramatization resources, such as ATP, allowed bringing out the suffering and humiliation resulting from violence and raising awareness of the abuse suffered, strengthening the sense of self-esteem and inner freedom through group support. This work was conducted with financial support from the National Council for Scientific and Technological Development (CNPq)